Determination of bioclimatic comfort areas in landscape planning: A case study of Cide Coastline - Mehmet Cetin (Turkish Journal of Agriculture: Food Science and Technology, 2016)
People are with overall nominal temperature, precipitation, humidity and where in certain ranges of environmental conditions such as wind they feel healthy and dynamic. In the appropriate range for the people of these values it is called the bioclimatic comfort. When bioclimatic comfort area is in the range of fair value would bother people in the area and want to get away from the area. Hence bioclimatic comfort areas used for the purpose of tourism is very important. In this study, Kastamonu-Cide bioclimatic comfort is done mapping of the coastline and thus aimed at building pad similar studies of a similar nature in the coastal areas. For this purpose, the region's climate data Cide is located; equivalent temperature according to the physiological index is bioclimatic comfort maps were prepared. To determine the structure of the field is bioclimatic comfort is collected climatic data from meteorological stations. The obtained data were evaluated by means of Rayman 1.2 and geographic information system (GIS) is used to produce thermal perception map with the help of software. According to the psychological equivalent temperatures As a result, the most appropriate time and area for outdoor recreation activities have been identified by thermal perception maps.